Enhanced circular dichroism of sparse nanoobjects by localized superchiral optical field. (4th May 2021) - Rui, Guanghao; Ying, Xinyuan; Zou, Shuting; Gu, Bing; Cui, Yiping
Abstract: The spectroscopic methods of circular dichroism (CD) is commonly used in analysing the chirality of molecules, which plays an important role in pharmaceutical compounds. However, the current methods require high sample density due to the weak CD effect of natural material, making it challenging to detect the signal of individual chiral molecule. In this work, we propose a technique to enhance CD signal of individual chiral molecule with the use of superchiral optical field, which is acquired by focusing a twisted radially polarized vortex onto a one-dimensional photonic band gap structure. Through adjusting the topological charge and the focusing angle of the illumination, a deep subwavelength optical field with full width at half maxima (FWHM) of 0.02 λ and 22.4-fold superchirality factor enhancement can be generated. In addition, we demonstrate that up to 20-fold CD enhancement can be obtained by introducing 2 nm on-resonant chiral molecule into the superchiral optical field. This finding will have widely potential applications in CD spectroscopy and superresolution imaging for sparse subdiffraction chiral objects.